THE STATE OF NITROXIDE PRODUCTION FUNCTION OF ENDOTHELIUM AND LEFT VENTRICLE HYPERTROPHY IN ARTERIAL HYPERTENSION - V. I. Podzolkov; A. E. Bragina; G. I. v; N. A. Murashko (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To assess levels of stable nitric oxide metabolites (NO) in plasma of arterial hypertension (AH) patients not taking systematic antihypertension therapy, in accordance with the presence and absence of the left ventricle hypertrophy (LVH).Material and methods. Totally, 124 AH patients included: 45 males, 79 females, mean age — 51,4±6,5 y.o., mean duration of AH — 7,9±7,3 y. Controls included 25 healthy persons: 10 males, 15 females; mean age — 48,2±7,8 y.o. Transthoracal echocardiography was done by standard method. Myocardium remodelling types were evaluated by the Ganau A (1992) criteria. Concentration of NO in plasma was measured by spectrophotometry. Statistics was done with Statistica 8.0 software.Results. In AH patients the level of NO was significantly higher than in controls — 43,2±21,7 mcM/L vs 28,3±9,6 mcM/L (p<0,05). There was positive correlation of NO with the fact of AH (r=0,31, p<0,05). In AH patients LVH was diagnosed in 66,7%. In AH with LVH patients concentration of NO was significantly higher than in AH non-LVH — 49,9±19,3 vs 39,8±18,3 mcM/L, respectively, (р<0,05) and in controls. There were direct correlations in AH patients, with NO and myocardial mass index of the left ventricle (LV) (r=0,44, р<0,05), with interventricular septum thickness (r=0,36, р<0,05), posterior LV wall thickness (r=0,44, р<0,05). In the subgroup of AH patients with normal LV geometry there were the lowest NO levels — 35,1±17,3 mcM/L. In subgroups of AH patients with concentric remodeling, eccentric remodeling and concentric LVH, levels of NO were significantly higher than in controls (p<0,05). Higher NO levels were found in AH patients with concentric LVH (53,9±19,1 mcM/L).Conclusion. In AH patients of I-II stages there were raised NO levels. In AH patients with LVH concentration of NO is significantly higher than in non-LVH. There is correlation with myocardium mass index of LV and NO (r=0,44, p<0,05). The highest levels of NO were found in AH patients with concentric LVH.